Teacher preparation in Papua New Guinea : past and present - O'Donoghue, Tom; Mortimer, John (Emerald Publishing Limited, 2024)
Presenting a comprehensive examination of the historical origins and development of schooling and teacher preparation in Papua New Guinea (PNG), the authors explore the unique education history of PNG - starting from indigenous education in villages, the influence of European colonization and the role of missionaries in providing education, and the implications for education policies and practices. Employing a thematic approach, the introduction provides an overview of the historical and cultural background of schooling and teacher preparation in PNG. Dedicated chapters then delve into specific historical periods, including the stage of conversion (1873-1945), the stage of gradualism (1946-1958), a growing nationalism (1959-1975), general education developments (1975-1992), teacher education developments (1975-1992), and developments to the present. Examining the education landscape during the respective period, highlighting key events, policies, and changes in teacher preparation, O'Donoghue and Mortimer utilise archival evidence, policy analysis, and historical narratives to present a comprehensive account of teacher education in PNG. Teacher Preparation in Papua New Guinea places the historical analysis within a global context, drawing parallels between PNG's experiences and those of other colonial and post-colonial societies.
Includes index.
Keywords: Teachers -- Training of -- Papua New Guinea.; Education, Teacher Training & Certification.; Teaching staff.; Teacher training.; elektronické knihy; electronic books